2015
DOI: 10.1038/nchem.2365
|View full text |Cite
|
Sign up to set email alerts
|

Iron sensitizer converts light to electrons with 92% yield

Abstract: Solar energy conversion in photovoltaics or photocatalysis involves light harvesting, or sensitization, of a semiconductor or catalyst as a first step. Rare elements are frequently used for this purpose, but they are obviously not ideal for large-scale implementation. Great efforts have been made to replace the widely used ruthenium with more abundant analogues like iron, but without much success due to the very short-lived excited states of the resulting iron complexes. Here, we describe the development of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
299
5
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(327 citation statements)
references
References 49 publications
(69 reference statements)
17
299
5
6
Order By: Relevance
“…Despite their good optical and photophysical properties, both the poor performance of the C4 complex and the extremely low photocurrents measured for C2 point to a nonoptimal interfacial charge separation process, possibly associated with a fast recombination mechanism occurring in the pico-and nanosecond timescale. These suggestions suppose that the relatively high injection yield reported by Wärnmark [26] for C2 grafted on TiO2 is valid in our systems. Indeed, and as compared to the typical 50 ps time window required for complete charge injection of the Ru N719 dye [39], the excited-state lifetimes of C2 and C4 in acetonitrile (16 and 26 ps, respectively), should afford a PCE (Photon Conversion Efficiency) > 1%.…”
Section: Homoleptic Complexesmentioning
confidence: 73%
See 1 more Smart Citation
“…Despite their good optical and photophysical properties, both the poor performance of the C4 complex and the extremely low photocurrents measured for C2 point to a nonoptimal interfacial charge separation process, possibly associated with a fast recombination mechanism occurring in the pico-and nanosecond timescale. These suggestions suppose that the relatively high injection yield reported by Wärnmark [26] for C2 grafted on TiO2 is valid in our systems. Indeed, and as compared to the typical 50 ps time window required for complete charge injection of the Ru N719 dye [39], the excited-state lifetimes of C2 and C4 in acetonitrile (16 and 26 ps, respectively), should afford a PCE (Photon Conversion Efficiency) > 1%.…”
Section: Homoleptic Complexesmentioning
confidence: 73%
“…Recently, as shown by Wärnmark and coworkers, N-heterocyclic carbenes (NHC) have been proven to promote notable improvements of 3 MLCT lifetimes, thanks to strong σ-donating effects inducing the destabilization of MC states [25][26][27][28]. While no DSSCs have been built from the newly designed complexes, this work has fostered the revival of research towards the development of iron-based sensitizers for DSSCs, which has been almost asleep since the pioneering works by Ferrere using the Fe(dcbpy) 2 (CN) 2 dye [14].…”
Section: Introductionmentioning
confidence: 99%
“…5 ,6 Increasingly NHC-based pincer complexes are also becoming recognised for their useful photophysical properties: ruthenium-based C, for example, is notable for microsecond 3 MLCT excited-state lifetimes, three orders of magnitude higher than [Ru(terpyridine) 2 ] 2+ . 7,8 Chart 1: Selected examples of NHC-based pincer complexes…”
Section: Introductionmentioning
confidence: 99%
“…The time constant for excited state electron injection into the mesoporous TiO 2 thin films commonly used in DSSCs was found to be about 3 ps, which is consistent with 490% reported yield. 2 Indeed, a variety of spectroscopic measurements provided strong evidence of nearly quantitative excited state interfacial electron transfer to TiO 2 . It is abundantly clear that an iron compound has finally been discovered that efficiently transfers electrons when illuminated with visible light!…”
mentioning
confidence: 99%
“…In the final analysis, iron consistently continues to disappoint and one can safely conclude that it is best to keep iron out of solar cells. Until now Harlang et al 2 found that the iron compound shown in Figure 1 harvests sunlight through most of the visible region with subsequent excited state electron transfer to a TiO 2 semiconductor with efficiencies 490%. Such a breakthrough in efficiency is remarkable, particularly when one considers the decades of prior research that failed to accomplish anything even close.…”
mentioning
confidence: 99%